Chronic Cadmium Exposure Alters Cardiac Matrix Metalloproteinases in the Heart of Sprague-Dawley Rat - Das, Sandra Concepcion; Varadharajan, Kavitha; Shanmugakonar, Muralitharan; Al-Naemi, Hamda A. (Frontiers in Pharmacology, 2021)
The aim of this study was to evaluate the role of chronic cadmium exposure in modulating cardiac matrix metalloproteinases (MMPs) in the heart of rats. Adult male Sprague-Dawley rats were exposed to 15 ppm CdCl2 in drinking water for 10 weeks followed by withdrawal of cadmium treatment for 4 weeks. Following the completion of the treatment, gene expression of inflammatory mediators (IL-1β, IL-6, IL-10, TNF-α and NF-κB), protein expression of MMP-2, MMP-9 and their respective inhibitors- TIMP-1 and TIMP-2, and gelatinolytic activity of MMP-2 and MMP-9 were determined. At the protein level, cadmium incites a differential effect on the expression and activity of gelatinases and their endogenous inhibitors in an exposure-dependent manner. Results also show that the administered cadmium dose elicits an inflammatory response until week 10 that slightly diminishes after 4 weeks. This study provides evidence of cadmium-induced imbalance in the MMP-TIMP system in the cardiac tissue. This imbalance may be mediated by cadmium-induced inflammation that could contribute to various cardiovascular pathologies.